2015
DOI: 10.1002/sia.5766
|View full text |Cite
|
Sign up to set email alerts
|

AuN films - structure and chemical binding

Abstract: AuN films were produced on 304 stainless steel using an arc‐pulsed – assisted plasma physical vapor deposition system. The deposition was performed using an Au target in a nitrogen atmosphere at different pressures. The films were characterized using x‐ray photoelectron spectroscopy and x‐ray diffraction. A 398.1‐eV binding energy was observed and assigned to gold nitride species. The x‐ray diffraction patterns displayed a crystallographic structure that corresponded to the Au‐fcc phase with broad diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…The literature has reported binding energies of 398.4 eV (near energy observed to S5, shown in Figure A) for RuN components . Energies of approximately 397.5 eV can be attributed to RuN components because values between 396.0 and 398.0 eV are characteristic of nitrogen hybridization with transition metals . Binding energies near 398.8 eV are typical of oxynitrides .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The literature has reported binding energies of 398.4 eV (near energy observed to S5, shown in Figure A) for RuN components . Energies of approximately 397.5 eV can be attributed to RuN components because values between 396.0 and 398.0 eV are characteristic of nitrogen hybridization with transition metals . Binding energies near 398.8 eV are typical of oxynitrides .…”
Section: Resultsmentioning
confidence: 91%
“…In the case of the final peaks of the high‐resolution Ru3d spectra, the envelope curve does not fulfill the experimental data; this behavior is because peaks exhibit asymmetries and tails that are not totally fulfilled by the Shirley Background. For this reason, Doniach Sunjic line shape method was applied to deconvolute these peaks; furthermore, in the literature, it is reported that peaks belonging to noble metals do not exhibit significant changes when they are bonded with low concentrations of nitrogen . Because in all cases, nitrogen is present at lower percentages than Ru, even after the SE process, it can be concluded that the films are mainly composed of a metallic phase.…”
Section: Resultsmentioning
confidence: 99%
“…Displacements, shifts to the higher or lower Bragg angles with respect to the PDF pattern, can be observed commonly in thin films for a compressive stress or tensile stress (Li et al ., 1998). Asymmetry can be due to a new phase in interstitial sites, causing the lattice planes to be unbalanced or resulting/deriving in a mechanical flexion of the crystal (Quintero et al ., 2015). Apparently, the factor for the SiNWs asymmetry is silver depositing on the SiNWs to cause mechanical flexion of SiNWs.…”
Section: Resultsmentioning
confidence: 99%
“…In C1s: C, 16 CO, 17 CN, 18 CO 3 . 19 In N1s: MeN (metal nitride), 20,21 CN, 22 CNO, 23 CN and NO, 24,25 to blocking the slip grain border. 47 If the temperature is continuously increasing, the presence of the CO 2 would accelerate the corrosion on the surface and increase the roughness such that the hardness falls abruptly 8 ; besides, the displacement produced by O atoms would have a decisive effect on the oxidation behavior.…”
Section: Results and Analysismentioning
confidence: 99%
“…In C1s: C, 16 CO, 17 CN, 18 CO 3 19 . In N1s: MeN (metal nitride), 20,21 CN, 22 CNO, 23 CN and NO, 24,25 NO, 26 N 2 , 27 NO 2 26 . In O1s: O 2 , 28 C x O y , 29 TiO 2 and ZrO 2 , 30 TiNO x , 31 TiO, 18 CNO, 23 NO x , 32 CO 33 .…”
Section: Results and Analysismentioning
confidence: 99%